2017
DOI: 10.1007/s00415-017-8489-9
|View full text |Cite
|
Sign up to set email alerts
|

Driving with a neurodegenerative disorder: an overview of the current literature

Abstract: Driving is important for employment, social activities, and for the feeling of independence. The decision to cease driving affects the quality of life and has been associated with reduced mobility, social isolation, and sadness. Patients with neurodegenerative disorders can experience difficulties while driving due to their cognitive, motor, and behavioral impairments. The aim of this review is to summarize the available literature on changes in driving competence and behavior in patients with neurodegenerativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 110 publications
0
24
0
1
Order By: Relevance
“…One should be very careful in arguing that it can be temporarily advised to drive for patients with AD based on an MMSE score ≥ 25, which was proposed by Versijpt and colleagues [ 7 ]. The MMSE is a short screening for global cognitive functioning, which may insufficiently cover several cognitive domains that are highly relevant for driving, namely visuospatial abilities and executive functions [ 14 , 15 , 23 , 24 ]. Patients with cognitive impairments in these domains may be unsafe drivers, even when having high MMSE scores due to relatively preserved orientation and language functions.…”
Section: Discussionmentioning
confidence: 99%
“…One should be very careful in arguing that it can be temporarily advised to drive for patients with AD based on an MMSE score ≥ 25, which was proposed by Versijpt and colleagues [ 7 ]. The MMSE is a short screening for global cognitive functioning, which may insufficiently cover several cognitive domains that are highly relevant for driving, namely visuospatial abilities and executive functions [ 14 , 15 , 23 , 24 ]. Patients with cognitive impairments in these domains may be unsafe drivers, even when having high MMSE scores due to relatively preserved orientation and language functions.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, we suggest that assessing emotion recognition may be a valuable supplement in the assessment of fitness to drive in patients with an NDD. This can be helpful, because finding contributing factors to the fitness to drive in these patients is still a topic of ongoing debate (Jacobs, Hart, & Roos, 2017). Future studies are needed to extend these results by looking at the role of facial emotion recognition in risk-taking behavior in on-road driving behavior and to investigate this relationship in the separate NDD patient groups.…”
Section: Discussionmentioning
confidence: 99%
“…Studies assessing driving competence in HD patients also showed that visual processing speed, visual scanning, and visual attention are more sensitive predictors of performance on on-road driving assessments, compared to motor functioning. 83,84 The assessment of visual cognitive impairment is therefore of clinical importance as it can have implications in daily functioning, such as the impact on driving performance, the use of electronic devices and subsequently affects participating in social activities. For example, the impairment to recognize negative facial emotions, such as anger, disgust and fear, could affect communication and social relationships.…”
Section: Discussionmentioning
confidence: 99%